THE EVOLUTION OF THE MACROECONOMIC STABILISATION PENTAGON IN ROMANIA, CZECH REPUBLIC AND HUNGARY - Ionita Rodica Oana (Annals of the University of Oradea: Economic Science, 2015)
This paper aims to achieve the pentagon analysis of macroeconomic stabilization in Romania, Czech Republic and Hungary in the period 2000 to 2013. It is a comparative analysis of the countries above mentioned in terms of the five key targets of economic policy, aiming the increasing, dynamic balance of each economy: economic growth rate, unemployment rate, inflation rate, the budget deficit as a percentage of Gross Domestic Product, the current account deficit of the balance of payments as a percentage of Gross Domestic Product. The main objective of each economy which passes from planned to market economy should be to cease the economic decline, followed by the elimination of internal and external imbalances and only after that it should be followed by a continuous growth process. All the above mentioned indicators shall be represented on an ad hoc graduated scale. The period of research was chosen so as to obtain a view of the macroeconomic policies in transition from one period to another, in order to highlight the common as well as the main differences in the approach used for economy stabilization. Therefore I have computed the graphical analysis of macroeconomic stabilization pentagon for the three countries in the period 2000- 2013 to captures the dynamics of the economic policy mix. This benchmark tool shows the interdependence which exists between inflation and other important economic indicators. The events occurred in the period starting with 2007/2008 have raised the interest of economics researchers, highlighting the need for significant improvements in the surveillance of the economic and financial system. The global fragility generated concerns regarding the vulnerabilities and causes which led to the occurrence of such events, thus generating different measurement techniques. Despite all its advantages, this approach has a significant limitation consisting in the fact that it can only reveal a picture without surprising other imbalances that can create un-sustainability in the economy.